Workplace bullying and redress procedures: experiences of teachers in Ireland. Issue 1 (12th March 2018) - Mannix McNamara, Patricia; Fitzpatrick, Kathleen; MacCurtain, Sarah; O'Brien, Michael
Abstract : Purpose: The purpose of this paper is to report the experiences of redress seeking and organisational responses for targets of bullying. Design/methodology/approach: A phenomenological research design was adopted. In total, 22 primary teachers (seven males, 15 females) in Ireland were self-selected for interview, following an advertisement detailing the study in a national teacher union magazine. Data were analysed utilising an interpretative phenomenological analysis framework. Findings: All those interviewed had made official complaints as per available procedures for addressing workplace bullying in their schools. All participants had engaged in Stages 1 and 2 of the official complaints procedures including uptake of recommended counselling. Three participants ceased engagement at Stage 2. In total, 18 participants had engaged in Stage 3 with 12 ceasing engagement at this stage. Seven participants had proceeded to Stage 4. It is noteworthy that no participant articulated satisfaction with the outcome, but conversely all had articulated further upset and acceptance of the reality that redress would not be forthcoming. These participants who had exercised agency in attempting to seek redress were met with power abuses and cultures of collusion. Research limitations/implications: This is a small-scale study with self-selecting teachers. The data point to some problematic assumptions underpinning anti-bullying policies in small organisations. Originality/value: This paper contributes to discourses of power/agency in workplace bullying. It challenges researchers and policy makers to elucidate more carefully the issues surrounding seeking redress for bullying.